Упростите выражение :-b2c(4b-c2) (4b+c2) +16b4c

QueenMarceline QueenMarceline    2   02.09.2021 14:21    0

Ответы
TipsSpeed TipsSpeed  02.09.2021 14:30

- {b}^{2} \times c \times (4b - {c}^{2} ) \times (4b + {c}^{2} ) + 16 {b}^{4} \times c = - {b}^{2} \times c \times {( {(4b)}^{2} - {( {c}^{2} )}^{2} )} + 16 {b}^{4} \times c = - {b}^{2} \times c \times (16 {b}^{2} - {c}^{4} ) + 16 {b}^{4} \times c = - 16 {b}^{4} c + {b}^{2} {c}^{5} + 16 {b}^{4} c = {b}^{2} {c}^{5}

здесь использовалась формула:

{a}^{2} - {b}^{2} = (a + b)(a - b)

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика